Potret Kehidupan Pedagang Di Pasar Buah Bantaran Anak Sungai Veteran Kelurahan Pengambangan Kecamatan Banjarmasin Timur - Simon, Rafa Irwina; Apriati, Yuli; Widaty, Cucu (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2024)
The Bantaran Anak Sungai Veteran Fruit Market is one of the fruit markets in East Banjarmasin. There are divisions of days for traders who trade on the market. This research aims to find out about the portrait of traders' lives at the Bantaran Anak Sungai Veteran fruit market, namely daily activities and trading activities. The method used in this research is qualitative method. The data sources used were primary and secondary data, informants were selected using purposive sampling with six informants. Data collection techniques use observation, interviews and documentation. The data collection technique in this research was carried out using analytical techniques using qualitative analysis with data reduction steps, data presentation and conclusions. The research results show that: (1) daily activities carried out by traders are divided into five times, namely activities carried out by traders at dawn, morning, afternoon, evening and night. (2) Trading activities are divided into three, namely: preparation for trading, starting with opening the tarpaulin, cleaning the trading stall, arranging fruits and vegetables according to their type. The trading process carried out by fruit traders is how to attract customers and haggle over prices. Finishing trading includes: calculating expenses and income, sorting fruit that is still good and almost yellowish, arranging the fruit in a basket, and covering the trade using a used tarpaulin or banner.